Faktor Risiko Osteoartritis Lutut dan Kualitas Hidup Pasien: Dari Kerusakan Sendi Menuju Beban Hidup Sehari-hari - Raymond R. Tjandrawinata (MEDICINUS, 2026)
Knee osteoarthritis is a whole-joint disease leading not only to structural damage but also to pain, functional limitations, impaired daily activities, and reduced quality of life. This article discusses the association between various major risk factors for knee osteoarthritis, including advanced age, obesity, female sex, history of knee injury, repetitive mechanical loading, muscle weakness, joint malalignment, and metabolic comorbidities, with patients’ quality of life. The severity of radiographic findings in knee osteoarthritis does not always correlate with the intensity of pain or functional limitations experienced by patients. Therefore, assessment and management should be oriented toward improving patients’ function and quality of life through education, physical exercise, weight management, rational pharmacological treatment, and selective intraarticular interventions. Treatment success should ultimately be evaluated based on its ability to improve patients’ mobility, independence, and social participation.